1996
DOI: 10.1007/bf01691151
|View full text |Cite
|
Sign up to set email alerts
|

Chronic meningitis due to herpes simplex virus in an immunocompetent host

Abstract: Herpes simplex virus (HSV) typically causes mucocutaneous disease, encephalitis, and acute men ingitis. There have been no previous reports of chronic meningitis due to this virus. A case of chronic meningitis due to herpes simplex virus type 2 (HSV-2) in a previously healthy 35-year-old woman whose predominant symptoms were headache and meningism without fever is described. Analysis of cerebrospinal fluid (CSF) revealed a lymphocytic pleocytosis, elevated protein, and hypoglycorrhachia. The diagnosis of herpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
2
7
0
1
Order By: Relevance
“…Hypoglycorrhachia has previously been reported in HSM (4,7,8,14). In our study, slightly increased lactate levels and lowered CSF/serum glucose ratios were found with a small proportion of HSM patients, in agreement with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…Hypoglycorrhachia has previously been reported in HSM (4,7,8,14). In our study, slightly increased lactate levels and lowered CSF/serum glucose ratios were found with a small proportion of HSM patients, in agreement with previous reports.…”
Section: Discussionsupporting
confidence: 93%
“…4,5,6,7 Our study supports finding of hypoglycorrachia associated with viral causes such as HSV, VZV and CMV.…”
Section: Discussionsupporting
confidence: 84%
“…1,2 In order to have a reliable CSF to serum glucose ratio, the time between the two determinations should be done within 60 minutes of each other. 2 Hypoglycorrhachia is usually suggestive of bacterial, tuberculous and fungal meningitis but has been reported in other cases such as in viral/aseptic meningitis 4–7 , leptomeningeal carcinomatosis 8 , subarachnoid hemorrhage 9 , Lyme meningitis 10 , neurobrucellosis 11 , and neurosarcoidosis 12 . The only study to our knowledge that has evaluated the differential diagnosis of hypoglycorrhachia was done in children and published in 1976 before the advent of molecular diagnostic tests 13 .…”
Section: Introductionmentioning
confidence: 99%
“…120 Neurologic disorders include longstanding active HSV encephalitis, 121 VZV-related chronic myelitis with chronic unilateral periauricular and facial pain, 122 active chronic VZV infection with chronic radicular sacraldistribution pain, cervical-distribution zoster paresis, and thoracic-distribution myelopathy, 123 chronic VZV ganglionitis-related postherpetic neuralgia, 124 and chronic HSV-2 meningitis. 125 TK-dependent antiviral resistance also frequently complicates extracutaneous HSV and VZV chronic infections.…”
Section: Extracutaneous Chronic Hsv and Vzv Infectionsmentioning
confidence: 99%